E-book de orientações multidisciplinares da equipe de assistência à saúde às pessoas idosas com a COVID-19 na alta hospitalar - Sousa, Wendy Chrystyan Medeiros de (2022)
Introduction: In the context of the COVID-19 pandemic, the elderly population has become highlighted for presenting potential risk, due to changes resulting from aging and the need for hospitalization; prevention and health promotion strategies can be useful, to favor these people in the post-hospital discharge stage, with multidisciplinary guidelines, which are important for the elderly and/or their family members/caregivers to feel safe and welcomed at the time of post-COVID-19 discharge. Objective: To analyze the multidisciplinary guidelines provided by the health care team to elderly patients with COVID-19, from the perspective of hospital discharge. Method: Methodological study, with a quantitative and descriptive approach, with the use of technological development, carried out in three stages: 1. review of the scientific literature on the subject, data collection with the health professionals of the hospital institution and, also, with family members/ elderly caregivers to identify the main multidisciplinary guidelines offered at the time of post-COVID-19 hospital discharge; 2. analysis of the contents obtained with the compilation of the main multidisciplinary orientations and 3. construction of the technological product. Results: The review considered the characteristics of COVID-19, health care for the elderly with COVID19, qualified discharge for continuity of care and health education, bringing updated texts on the subject. Data collection carried out both with health professionals, obtaining the main guidelines given to elderly patients at hospital discharge, and with elderly patients and/or their family members/caregivers, showing that most of the guidelines given were cited by these people and also coincide with the findings of the consulted literature. The comparison of the information obtained was analyzed and, subsequently, an educational technological product was planned and built, based on the principles of health education and public guidelines regarding COVID-19, an interactive E-book entitled “E-book of Multidisciplinary Guidelines After Hospital Discharge for Elderly People with COVID-19”, containing multidisciplinary guidance from professionals in Nursing, Pharmacy, Physiotherapy, Speech Therapy, Medicine, Nutrition, Dentistry, Psychology, Social Work and Occupational Therapy. Final Considerations: There was a scarcity of publications on the subject of multidisciplinary guidelines for elderly people after COVID-19 in the hospital discharge process, and the recommendations mentioned by the professionals consulted were more complete than those in the literature. Educational materials are important devices in the prevention and promotion of health for post-COVID-19 elderly patients and it is expected that the interactive E-book will help the elderly and their family members/caregivers to feel instructed to continue the care, after hospital discharge.